2020
DOI: 10.3390/ijerph17051676
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Qualities of a Recreational Forest: Findings from the Cross-Sectional Hallerwald Case Study

Abstract: Prior research shows that forests contribute to human health and well-being. In this sense, this cross-sectional case study, adopting the principles of citizen science, assessed the restorative potential of places in the Hallerwald, an Austrian community forest. A convenience sample of adult forest visitors (n = 99, 64% females) completed a survey during a guided 2.5 h forest tour. The German questionnaire assessed the qualities of defined places in the forest. We also investigated changes in mood states, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
0
24
1
Order By: Relevance
“…Prior studies highlighted the recreational value of forests and urban parks before and also during the crisis [ 23 , 24 , 25 , 26 ]. Robinson et al found that people spent more time in nature for health and wellbeing benefits and felt that nature helped them to manage the COVID-19 pandemic [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies highlighted the recreational value of forests and urban parks before and also during the crisis [ 23 , 24 , 25 , 26 ]. Robinson et al found that people spent more time in nature for health and wellbeing benefits and felt that nature helped them to manage the COVID-19 pandemic [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only the following five exceptions of the ban to enter public places applied: activities to avert an immediate danger to life, limb, or property; professional activity; shopping to cover necessary basic needs; care and assistance for people in need of support; and exercising outdoors alone and with pets or people living in the same household. Especially, the latter exception acknowledged prior studies showing that contact to outdoor nature can positively influence human health and wellbeing [ 16 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, it would also be interesting to compare these groups with others doing activities in green spaces (i.e., forest walking guided tours, recreational walks, interactive study of local fauna and flora, etc. ), as many studies have also reported beneficial outcomes of green spaces for mental health [40,59,60]. Moreover, we assumed that every subject was its own control before participating in the activity and failed to take into account the number of days each subject had been exposed to the blue space previous to the interview.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…As such, methods that can effectively relieve stress and induce physical and mental relaxation are needed. Stress relief that results from interactions with nature, particularly with forests, has been the focus of significant research; recent studies report that these interactions have an important and positive effect on human health [11][12][13][14][15]. Current scientific evidence has helped to establish the field of forest therapy, which is an evidence-based method used to promote human health via an experience known as "forest bathing".…”
Section: Introductionmentioning
confidence: 99%